2019
DOI: 10.17126/joralres.2019.042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge of oral cancer in dentists in the Los Ríos Region, Chile, in 2017

Abstract: The alteration of the vertical dimension can deteriorate the facial harmony, and it can be measured through objective and subjective methods, although many of which are not reliable. Objective: Relate the anthropometric fingers length with the measurement of the vertical occlusal dimension (VOD). Material and Methods: Cross-sectional, observational study that included 114 students from the School of Dentistry with class I malocclusion and complete dentition. The VOD was evaluated as the measurement between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Research conducted by Torres et al (2020) in the Peruvian population regarding the correlation between VDO and the length of the fingers, obtained the result that there was a correlation between VDO and the length of the middle finger with a correlation coefficient value of 0.31. 24 Research by Nazir S et al (2015) also obtained results of a correlation between VDO and the length of the middle finger in males with a value of r = 0.363. 8 Both studies stated that there was a correlation between VDO and the length of the middle finger.…”
Section: Discussionmentioning
confidence: 87%
“…Research conducted by Torres et al (2020) in the Peruvian population regarding the correlation between VDO and the length of the fingers, obtained the result that there was a correlation between VDO and the length of the middle finger with a correlation coefficient value of 0.31. 24 Research by Nazir S et al (2015) also obtained results of a correlation between VDO and the length of the middle finger in males with a value of r = 0.363. 8 Both studies stated that there was a correlation between VDO and the length of the middle finger.…”
Section: Discussionmentioning
confidence: 87%
“…Other anthropometric approaches for finding the correlation between VDO and finger length were used independently by Bhandari's and Sihuay-Torres's teams [29,95,96]. Bhandari et al suggested that the little finger length almost equals the VDO, but although Sihuay-Torres et al found a correlation between the index, middle and little finger and the VDO, they still recommended the method as a supplementary one [95,96]. Since no ongoing research has confirmed the scientific value and reliability of these methods, they should be performed cautiously or confirmed with the corresponding methods.…”
Section: Additional Methodsmentioning
confidence: 99%